1988
DOI: 10.1037/h0091733
|View full text |Cite
|
Sign up to set email alerts
|

MMPI profiles of patients who endorse multiple partial seizure symptoms.

Abstract: This investigation was concerned with the MMPI profiles of 40 patients who reported multiple symptoms of partial seizure-like phenomena and had abnormal EEGs. The majority of this sample was presumed to have longstanding treatment-resistant psychiatric illnesses. Grossly abnormal MMPl profiles with multiple elevations were frequently observed, with 65% having significant elevations on at least six of the ten clinical scales. The mean group profile had seven significant scale elevations (i.e.,T-score >69). Of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
(34 reference statements)
1
4
0
Order By: Relevance
“…The grossly elevated MMPI profiles of patients who displayed elevated signs for the Epileptic Spectrum Disorder and deficient dichotic word listening were similar to the patterns reported by Roberts, et al (1988). The selfreports of marked improvement with Tegretol after no improvement with traditional antidepressants or worsening of symptoms with antipsychotic drugs also supports the results of Roberts' research team.…”
Section: Subjective Improvement Following Treatment With Carbamazepine (Tegretol) Forsupporting
confidence: 75%
See 2 more Smart Citations
“…The grossly elevated MMPI profiles of patients who displayed elevated signs for the Epileptic Spectrum Disorder and deficient dichotic word listening were similar to the patterns reported by Roberts, et al (1988). The selfreports of marked improvement with Tegretol after no improvement with traditional antidepressants or worsening of symptoms with antipsychotic drugs also supports the results of Roberts' research team.…”
Section: Subjective Improvement Following Treatment With Carbamazepine (Tegretol) Forsupporting
confidence: 75%
“…Such results suggc5r that many of the debilicating symptoms that persist for months to years after ;I traumatic brain injury may be electrical in nature rather than due to "psychological responses" and might be treatable by appropriate dosages of carbamazepine or other, e.g., Gabapentin (Neurontin) antiepilepuc compounds. Roberts, Paulsen, Marchman, and Varney (1988) reported that 13 of the 16 patients who were treated with the antiepileptic drug carbamazepine (Tegretol), a derivative of iminodibenzyl related structurally to the antidepressant irnipramine (Leppk, 1990), exhibited marked chical and psychometric improvement. These patients who had sustained brain traumas had been diagnosed for years with multiple psychiatric difficulties yet had not responded to traditional medications for these diagnostic categories.…”
Section: Subjective Improvement Following Treatment With Carbamazepine (Tegretol) Formentioning
confidence: 99%
See 1 more Smart Citation
“…Several groups of researchers (e.g., Livingston & Escobar, 1971;Persinger & Makarec, 1987; Roberts, Varney, Hulbert, Paulsen, Richardson, Springer, Smith-Shepard, Swan, Legrand, Harvey, & Strichen, 1990), using different methods and perspectives, have suggested that the behaviors and experiences of patients who display or who are inferred to display electrical lesions within the hippocampal-amygdaloid regions are extreme examples of the normal population. Roberts and associates (Roberts, Paulsen, Marchman, & Varney, 1988; Roberts, Varney, Hulbert, et al, 1990; Roberts, Varney, Paulsen, & Richardson, 1990) have shown repeatedly that patients who exhibit quantitative increases in complex partial epileptic-like signs also display dichotic listening deficits and multiple elevations on the MMPI. Both the dichotic listening and MMPI scores improve (Springer, Garvey, Varney, & Roberts, 1991) after treatment with the anticonvulsant carbamazepine (Tegretol).…”
Section: Discussionmentioning
confidence: 98%
“…Roberts and associates (Roberts, Paulsen, Marchman, & Varney, 1988;Roberts, Varney, Hulbert, et al, 1990;Roberts, Varney, Paulsen, & Richardson, 1990) have shown repeatedly that patients who exhibit quantitative increases in complex partial epileptic-like signs also display dichotic listening deficits and multiple elevations on the MMPI. Both the dichotic listening and MMPI scores improve (Springer, Garvey, Varney, & Roberts, 1991) after treatment with the anticonvulsant carbamazepine (Tegretol).…”
Section: Discussionmentioning
confidence: 99%